Implementation of Sinjai Regional Regulation Number 15 of 2017 Concerning the Protection and Empowerment of Farmers, Fishermen and Fish Farming - Usnidah Umar; Yudarti Yudarti; Hartati Malkab (LPPM Institut Studi Islam Sunan Doe, 2024)
The purpose of this study was to find out about the implementation of the local goverment regulation number 15 Of 2017 about protection and empowerment of farmers, fishermen and fish cultivators. The type of research is qualitative, data collection techniques is observation, interviews and documentation. Data analysis techniques were carried out by collecting data, reducing data, presenting data and drawing conclusions.The results of this study state that the implementation of the local government regulation number 15 of 2017 about protection and empowerment of farmers, fishermen and fish cultivators in Sinjai is not yet maximal yet. The purpose of protecting and empowering the farmers, and the fishermen is done systematically, integrated, directed, thorough, transparent, and accountable. Which in order to increase the prosperous of farmers and fishermento provide infrastructure of farmers and fishermens was not well implemented yet not on time or on good quality because of limitations of facilities from Department agriculture and department of fisheries.